From Agrarian Ritual to Profound Spiritual Experience: A Theological Interpretation of Pentecost in the Old and New Testaments - Utami, Salwa Adelia Arsyadani; Untung, Syamsul Hadi; Yahya, Yuangga Kurnia (BIA': Jurnal Teologi dan Pendidikan Kristen Kontekstual, 2025)
This study aims to explore and interpret the meaning of Pentecost by considering its historical, theological, and spiritual contexts. It employs a theological approach, qualitative research methods, and textual analysis to examine the relationship between symbolism and meaning in the celebration of Pentecost. The study shows that the meaning of Pentecost differs between the Old and New Testaments, reflecting a transition from an agrarian ritual to a profound spiritual experience in which the Holy Spirit actively participates in the lives of believers. Overall, Pentecost reflects the development of Christian faith from a traditional agrarian context to a more complex spiritual understanding of God's presence through the Holy Spirit. Thus, Pentecost is not only a historical celebration but also a theological statement about God's presence in the lives of His people.